The Protection of Motherhood - Irene Kamberidou (SPOTLIGHT, a Fortnightly Publication for Political Studies, Publication of the Institute of Political Studies (I.P.S), no. 8, Sept. 15, 1984: 8., 1984)
Kamberidou, Irene (1984). The Protection of Motherhood.  SPOTLIGHT, a Fortnightly Publication for Political Studies, Publication of the Institute of Political Studies (I.P.S),  no. 8, Sept. 15, 1984: 8.